Proceedings of 3DBODY.TECH 2019 - 10th International Conference and Exhibition on 3D Body Scanning and Processing Technologies, 2019
DOI: 10.15221/19.127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thermal Comfort of Clothing with Different Textile Material through Thermal Simulation

Abstract: Thermophysiological comfort is one of the most important aspects of wear comfort. Currently, there are no software solutions available for the combined consideration of material characteristics, fit and thermophysiological behavior. Thus, a laborious empirical process is typically required to determine an appropriate design matching new textile materials for pattern cuts as well as changing climatic conditions. A detailed wear trial in a climatic chamber supports this process. The objective of this research is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Similar to previous studies, the maximum temperature values of the upper back body garment surface were higher than those of the upper front body garment surface in almost all garments (Table 3). 40 The highest maximum values were measured in the cotton/polyester garment (CPS) during the first 30 min of activity. It was observed that sweating started in 20 minute period of time in the upper back body part as well as on the upper front body garment surface from the appearance of black colour from the histogram graphics.…”
Section: Temperature Sensor Skin Temperature and Thermal Camera Garme...mentioning
confidence: 99%
“…Similar to previous studies, the maximum temperature values of the upper back body garment surface were higher than those of the upper front body garment surface in almost all garments (Table 3). 40 The highest maximum values were measured in the cotton/polyester garment (CPS) during the first 30 min of activity. It was observed that sweating started in 20 minute period of time in the upper back body part as well as on the upper front body garment surface from the appearance of black colour from the histogram graphics.…”
Section: Temperature Sensor Skin Temperature and Thermal Camera Garme...mentioning
confidence: 99%
“…The human body continuously produces heat due to its metabolism. The metabolism rate depends upon the activity level of the human [7].…”
Section: Clothing Thermal Comfortmentioning
confidence: 99%
“…Thermophysiological models are used in many fields. In biometeorology, they were used to develop a universal climate index (UTCI) [6] to analyze and evaluate human thermal response under different clothing thermal resistance [24,25]. By combining thermophysiological models with thermal human models, a thermophysiological human simulator for clothing comfort analysis was developed [26].…”
Section: Introductionmentioning
confidence: 99%